1988
DOI: 10.1038/331723a0
|View full text |Cite
|
Sign up to set email alerts
|

Gene for a novel tRNA species that accepts L-serine and cotranslationally inserts selenocysteine

Abstract: The biological requirement of the trace element selenium was recognized 40 years ago. Selenium is incorporated into several enzymes and transfer RNA species of both prokaryotic and eukaryotic origin. In enzymes which contain a selenopolypeptide, selenium is present as covalently bound selenocysteine which participates in the catalytic reaction. Sequence analysis of the genes coding for two selenoproteins, formate dehydrogenase H from Escherichia coli and glutathione peroxidase from mouse and man, demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
218
0
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(221 citation statements)
references
References 20 publications
0
218
0
3
Order By: Relevance
“…As selenocysteine-containing proteins are found in all three kingdoms, to what extent are the mechanistic features inherent in one line of decent conserved in another? Current evidence supports a model in which the recognition of UGA as a selenocysteine codon, rather than a stop codon, is dependent upon the presence of mRNA secondary structures termed selenocysteine insertion sequence (SECIS) elements (Heider et al+, 1992; for review see Stadtman, 1996;Low & Berry, 1996;Atkins et al+, 1999)+ SECIS elements are RNA stemloop structures found immediately downstream of the selenocysteine-specific UGA codon in bacterial mRNAs, whereas, in mRNAs of eukaryotes and archaebacteria, SECIS elements are located in the 39 untranslated region, frequently at a considerable distance from the selenocysteine codon+ An outline of the biochemical pathway for selenocysteine insertion in bacteria has been elucidated by genetic and biochemical studies in which the products of the selA, sel B, sel C, and sel D genes are shown to be required for the insertion of selenocysteine at the di-rection of SECIS elements (Leinfelder et al+, 1988a(Leinfelder et al+, , 1988b(Leinfelder et al+, , 1989Forchhammer et al+, 1989Forchhammer et al+, , 1990)+ A key feature of this pathway involves the function of a specialized selenocysteine tRNA (tRNA Sec ; product of the sel C gene), which is initially charged with serine and subsequently converted to selenocysteyl-tRNA Sec (Baron & Böck, 1995)+ In correspondence to these factors, only tRNA Sec and the selenophosphate synthetase gene (homolog of sel D) have been identified in eukaryotes (Lee et al+, 1989;Low et al+, 1995)+ An important unanswered question is how, for eukaryotes, do the SECIS elements in the 39 untranslated region signal, at a distance, the cotranslational incorporation of selenocysteine at UGA codons? In particular, an understanding of the molecular link between tRNA Sec and SECIS RNA elements has remained elusive, in part, because the eukaryotic homolog of SELB has not yet been identified+ In a model proposed by Ringquist et al+ (1994) it is held that SELB delivers bacterial selenocysteyl-tRNA Sec to a ribosome-SECIS RNA complex+ This model implicitly accounts for the recognition of a selenocysteine codon by coupling the required SECIS RNA recognition event to the delivery of the charged tRNA+ In eukaryotes, the known elongation factor, EF-1a, fails to deliver selenocysteyltRNA Sec to the ribosome, and a partially characterized factor is implicated for this role (Jung et al+, 1994;Yamada, 1995)+ Recent progress has been made in the identification and cloning of a mammalian protein, dbpB, which recognizes SECIS RNA elements (Shen et al+, 1998)+ Nonetheless, a variety of proteins that have been detected in association with mammalian SECIS RNA elements, or by autoimmune antibodies that recognize tRNA Secprotein complexes, have yet to be fully characterized …”
Section: Introductionmentioning
confidence: 99%
“…As selenocysteine-containing proteins are found in all three kingdoms, to what extent are the mechanistic features inherent in one line of decent conserved in another? Current evidence supports a model in which the recognition of UGA as a selenocysteine codon, rather than a stop codon, is dependent upon the presence of mRNA secondary structures termed selenocysteine insertion sequence (SECIS) elements (Heider et al+, 1992; for review see Stadtman, 1996;Low & Berry, 1996;Atkins et al+, 1999)+ SECIS elements are RNA stemloop structures found immediately downstream of the selenocysteine-specific UGA codon in bacterial mRNAs, whereas, in mRNAs of eukaryotes and archaebacteria, SECIS elements are located in the 39 untranslated region, frequently at a considerable distance from the selenocysteine codon+ An outline of the biochemical pathway for selenocysteine insertion in bacteria has been elucidated by genetic and biochemical studies in which the products of the selA, sel B, sel C, and sel D genes are shown to be required for the insertion of selenocysteine at the di-rection of SECIS elements (Leinfelder et al+, 1988a(Leinfelder et al+, , 1988b(Leinfelder et al+, , 1989Forchhammer et al+, 1989Forchhammer et al+, , 1990)+ A key feature of this pathway involves the function of a specialized selenocysteine tRNA (tRNA Sec ; product of the sel C gene), which is initially charged with serine and subsequently converted to selenocysteyl-tRNA Sec (Baron & Böck, 1995)+ In correspondence to these factors, only tRNA Sec and the selenophosphate synthetase gene (homolog of sel D) have been identified in eukaryotes (Lee et al+, 1989;Low et al+, 1995)+ An important unanswered question is how, for eukaryotes, do the SECIS elements in the 39 untranslated region signal, at a distance, the cotranslational incorporation of selenocysteine at UGA codons? In particular, an understanding of the molecular link between tRNA Sec and SECIS RNA elements has remained elusive, in part, because the eukaryotic homolog of SELB has not yet been identified+ In a model proposed by Ringquist et al+ (1994) it is held that SELB delivers bacterial selenocysteyl-tRNA Sec to a ribosome-SECIS RNA complex+ This model implicitly accounts for the recognition of a selenocysteine codon by coupling the required SECIS RNA recognition event to the delivery of the charged tRNA+ In eukaryotes, the known elongation factor, EF-1a, fails to deliver selenocysteyltRNA Sec to the ribosome, and a partially characterized factor is implicated for this role (Jung et al+, 1994;Yamada, 1995)+ Recent progress has been made in the identification and cloning of a mammalian protein, dbpB, which recognizes SECIS RNA elements (Shen et al+, 1998)+ Nonetheless, a variety of proteins that have been detected in association with mammalian SECIS RNA elements, or by autoimmune antibodies that recognize tRNA Secprotein complexes, have yet to be fully characterized …”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, it was believed that there was no natural suppressor tRNA, however it was then shown that one of the genes (se/C) relating to the Correspondence address: T. Mizutani, Faculty of Pharmaceutical Sciences, Nagoya City University, Mizuho-ku, Nagoya 467, Japan synthesis of formate dehydrogenase corresponded to the UGA nonsense suppressor tRNA [7]. This tRNA was used in the cotranslational incorporation of selenocysteine into formate dehydrogenase [5] in which selenocysteine was present at the active site [ 1 J.…”
Section: Introductionmentioning
confidence: 99%
“…This tRNA was used in the cotranslational incorporation of selenocysteine into formate dehydrogenase [5] in which selenocysteine was present at the active site [ 1 J. It was suggested that this tRNA did not accept selenocysteine but serine [7]. However, the presence of suppressor tRNA in the cytosol of E. coli has not been shown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable examples of selenoproteins include glutathione peroxidase (5), iodothyronine deiodinase (1,6), and the mammalian plasma protein selenoprotein P (7). In Escherichia coli, three isoenzymes H, N, and O of the formate dehydrogenases contain a selenocysteine residue in their active sites; its cotranslational incorporation is directed by an in-frame UGA codon (8,9). Selenocysteyl-tRNA Sec , unlike all other tRNAs, is recognized by the special elongation factor (EF) SelB (10).…”
mentioning
confidence: 99%